A rare case of necrotising enterocolitis (NEC) in a full-term infant at 12 hours of age before the introduction of enteral feed (EF). (24th May 2012) - Gbinigie, H; Rao, V; Syed, S; Chuang, S
Abstract : We observed a case of NEC in a male term infant (TI), weighing 4.3 kg He was born by emergency caesarean section for fetal distress following an uneventful antenatal course. Offensive liquor was noted at delivery without other septic risk factors. He was born in poor condition but responded promptly to IPPV and was spontaneously breathing at 3 min age. APGARS were 4, 7 & 8 at 1, 5 &10 min respectively. He was admitted to NICU for persistent tachypnoea, requiring CPAP support. He received saline boluses for poor peripheral perfusion and was commenced on IV benzylpenicillin and gentamicin for presumed sepsis. He was noted to have bilious aspirates and brown-stools at 12 h age. Examination revealed mild abdominal distension with associated tenderness. Abdominal X-ray showed dilated bowel loops, widespread pneumatosis and portal-tract air. Blood indices were unremarkable. Exploratory laparotomy D1 confirmed NEC involving the entire colon and no malrotation. An ileostomy and mucus fistula were fashioned and no bowel resected He made an uneventful recovery. He was commenced on parenteral nutrition, kept nil-by-mouth and received a 10-day-course of antibiotics, including metroniadazole. Blood culture was negative and congenital heart disease (CHD) excluded. EF was initiated on D11 using breast milk and gradually increased. EF was changed to Pepti-junior on D24 due to high stoma losses and positive reducing substance. Full EF was established on D27. NEC is predominately a disease of preterm infants. Nonetheless, there have been documented cases in TI accounting for 10% neonatal NEC. It tends to involve TI with known risk factors e.g. intrauterine growth restriction, birth asphyxia, CHD, hypothyroidism, polycythaemia, sepsis and umbilical lines and EF introduced. Although the pathogenesis remains elusive, three major factors, pathogenic organism, EF, and bowel compromise, coalesce in at-risk neonates to produce bowel injury. There are minor variations in the clinical presentation in preterm- and term-NEC. The onset tends to be earlier in TI without outstanding thrombocytopenia and acidosis. This case report highlights the enigmatic presentation of term-NEC and need for vigilance in TI presenting with early respiratory distress/mild sepsis.